From Unfolded Sequences to Structural Motifs - Niel, Blanca Isabel (2011)
We consider that the biopolymer chain forms intramolecular contacts at the expense of losing conformational freedom. By means of a cohesive arithmetic method we have analysed the feasible base pairing contact patterns in nucleotide subsequences from untangled to knotted biopolymer chains. The procedure associates complementary integers to each of the two W-C base pairings of the four bases that integrate the homologous sequences. Given the number of the basic building blocks and the quantities of each of the nucleotides in the biopolymer, the unfolded sequence is obtained searching for the admissible Hamiltonian paths of different lengths under the penalisation of any zipping and/or stacking of base pairing processes. Finally, by comparing backward and forward readings in the obtained unfolded sequences we could individualize certain structural features of biological interest which are deployed in scientific papers about nucleic acids (J. P. Sheehy et. al., RNA, 16(2):417-429 (2010); A. Fernández, B. Niel and T. Burastero, Biophysical Chemistry, 74(2):89-98 ( 1998)).